2006
DOI: 10.1523/jneurosci.2947-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

The Biochemical and Neuroendocrine Bases of the Hyperalgesic Nocebo Effect

Abstract: Despite the increasing research on placebos in recent times, little is known about the nocebo effect, a phenomenon that is opposite to the placebo effect and whereby expectations of symptom worsening play a crucial role. By studying experimental ischemic arm pain in healthy volunteers and by using a neuropharmacological approach, we found that verbally induced nocebo hyperalgesia was associated to hyperactivity of the hypothalamic-pituitary-adrenal (HPA) axis, as assessed by means of adrenocorticotropic hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
255
4
17

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(283 citation statements)
references
References 56 publications
(84 reference statements)
7
255
4
17
Order By: Relevance
“…47,48 Administration of proglumide, a mixed CCK-A and B receptor antagonist reduces anxiety-induced facilitation of pain (i.e., nocebo hyperalgesia). 47,49 These data suggest two alternative possibilities. It is possible, as described above, that with time after surgery, the PCA button or tone becomes a safety signal that is associated with a CCK-mediated increase in pain and lockout interval demands.…”
Section: Discussionmentioning
confidence: 90%
“…47,48 Administration of proglumide, a mixed CCK-A and B receptor antagonist reduces anxiety-induced facilitation of pain (i.e., nocebo hyperalgesia). 47,49 These data suggest two alternative possibilities. It is possible, as described above, that with time after surgery, the PCA button or tone becomes a safety signal that is associated with a CCK-mediated increase in pain and lockout interval demands.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies have shown that nocebo hyperalgesic manipulations heighten HPA activity (Benedetti et al 2006, Johansen et al 2003, cortical activity in pain-related regions (Kong et al 2008;Bingel et al 2011;Schmid et al 2015), pain-related activity in the spinal 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 cord (Geuter & Buchel 2013), blood pressure and reported negative emotions combined with increased pain reports. The findings from the present study further add that successful induction of nocebo expectations increase negative emotions significantly enough to engage physiological and motivational defense systems (Grillon et al 1991), that enhance cortical alertness measured by startle responses.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, expecting a negative event, such as increased pain induced by nocebo suggestions should increase the startle response. A previous study (Benedetti et al 2006) demonstrated that nocebo suggestions increase hypothalamic-pituitary-adrenal (HPA) activity, showing that endocrine stress responses are core features of nocebo responses. Thus, information that pain will be increased may activate physiological defense systems that in turn can be measured as increased startle responses.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the CCK antagonist, proglumide, has been found to prevent nocebo hyperalgesia but not the hypothalamuspituitary-adrenal hyperactivity, which suggests two independent biochemical pathways activated by nocebo suggestions and anxiety (Benedetti, Amanzio, Vighetti & Asteggiano, 2006).…”
Section: Neurobiology Of Negative Expectationsmentioning
confidence: 96%